Characterization of QTLs for disease resistance and rolled leaf traits in a mutant derived wheat RIL population - Bian, Ruolin (Kansas State University, 2023)
Both biotic and abiotic stresses are major constraints for global wheat production. Abiotic stress such as drought and heat and biotic stress such as fungal and viral diseases can significantly reduce grain yield and quality of wheat. In this study, a mutant, named JagMut1095, identified from EMS treated Jagger cultivar, showed significant higher Type II resistance to Fusarium head blight (FHB) than Jagger in the greenhouse experiments. This mutant also showed obvious rolled leaf (RL) and BYDV susceptibility in contrast to Jagger in the field experiments. A population of 154 recombinant inbred lines (RILs) was developed from the cross of JagMut1095 x Jagger and was used for QTL analysis on these three traits. For Type II FHB resistance, 12 QTLs were identified on chromosomes 1B, 2B, 3A, 4B, 4D, 5A, 5B, 5D, 6A, 6B, 7A and 7B. One major QTL QFhb.hwwg-4BS was mapped in a 1.5 Mb interval in chromosome arm 4BS and explained up to 32.8% of the phenotypic variation. The QFhb.hwwg-4BS interval has 17 high confidence genes including Rht1, a ‘Green Revolution’ gene, and overlaps with the major QTL QPh.hwwg-4BS for plant height, thus, QPh.hwwg-4BS is most likely Rht-1B. QTL analysis on barley yellow dwarf (BYDV) data from the population identified one major QTL, QByd.hwwg-2DL, in a physical interval between 642,415,923 bp and 642,998,925 bp on chromosome arm 2DL and Jagger contributed the resistance allele. Two major QTLs (QRl.hwwg-1AS and QRl.hwwg-5AL) for RL were detected and together explained up to 61% of the phenotypic variation. The mutant contributed RL alleles at both QTLs. These major QTLs for RL and BYDV resistance in this study are novel and they provide the new genetic resources and insight for further characterization and utilization of these genes in breeding. Fine-mapping of QFhb.hwwg-4BS will facilitate further understanding of the genetic relationship between FHB resistance and plant height to improve wheat FHB resistance in semidwarf wheat cultivars.
Keywords: Wheat; FHB; Rolled leaf; BYDV; QTL